THE SIMULTANEITY BETWEEN TRADING VOLUME AND ORDER IMBALANCE (Case Studies of LQ 45) - Kusumastuti, Nurita; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to analyze the simultaneity between trading volume and order imbalance, the influence of past performance, market risk, market capitalization, tick size totrading volume and the influence of tick size, depth and bid-ask spread to order imbalance of companies were listed on LQ 45 index. Sample in this research were selected by using purposive sampling method with some selected criterias. 55 companies listed on 2014’s LQ 45 index were chosen as sample. The results showed that trading volume is simultaneously related to order imbalance; past performance, market risk and market capitalization have a positive and significant effect to trading volume, tick size has a negative and significant effect to trading volume, order imbalance has a negative and not significant effect to trading volume; tick size, depth, bid-ask spread, and trading volume have no significant effect to order imbalance.